A Study on the Effect of Environmental Stress Caused by Air Pollution on Cockerel Bird (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The air quality they reduce is significant, and their harmful impacts on people's health are welldocumented.Their impact on wildlife, especially birds like the cockerel, is still a topic of study andconcern. Cockerel birds face a predicament due to environmental stresses such air pollution from dieselgenerators, which may have far-reaching ecological effects. The effects of pollution on cockerel birds,have not received as much attention as they deserve. In this study, I looked at the risks that generatorspose in the form of noise and air pollution. There is rising concern in the contemporary world about thecomplex relationship between environmental stresses and the wellbeing of living creatures. The usage ofdiesel generators has greatly contributed to the rise in air pollution that has accompanied the growth ofindustry and urbanization. The air quality they reduce is significant, and their harmful impacts onpeople's health are well-documented. Their impact on wildlife, especially birds like the cockerel, is still atopic of study and concern. The current study was undertaken to educate the public on the dangersposed by generator-caused air pollution, which has been shown to reduce the nutritional value anddecrease the overall quality of chicken products.